2020
DOI: 10.1074/mcp.ra119.001829
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Adaption of Pseudomonas aeruginosa by Hacking Siderophores Produced by Other Microorganisms

Abstract: Bacteria secrete siderophores to access iron, a key nutrient poorly bioavailable and the source of strong competition between microorganisms in most biotopes. Many bacteria also use siderophores produced by other microorganisms (exosiderophores) in a piracy strategy. Pseudomonas aeruginosa, an opportunistic pathogen, produces two siderophores, pyoverdine and pyochelin, and is also able to use a panel of exosiderophores. We first investigated expression of the various iron-uptake pathways of P. aeruginosa in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(168 citation statements)
references
References 83 publications
9
159
0
Order By: Relevance
“…In fact, it has recently demonstrated that the expression of some proteins, including outer-membrane ones, may be affected by the environmental conditions. For instance, TonB-dependent transporters (TBDTs) present in the outer membranes of P. aeruginosa are induced under iron restricted conditions or when cells have been harvested from an infection model [51]. Although bacteria we analyzed in our work were grown in Mueller Hinton (MH) medium, far from the conditions adopted by Perraud et al, many TBDTs were identified also in our samples.…”
Section: Discussionmentioning
confidence: 90%
“…In fact, it has recently demonstrated that the expression of some proteins, including outer-membrane ones, may be affected by the environmental conditions. For instance, TonB-dependent transporters (TBDTs) present in the outer membranes of P. aeruginosa are induced under iron restricted conditions or when cells have been harvested from an infection model [51]. Although bacteria we analyzed in our work were grown in Mueller Hinton (MH) medium, far from the conditions adopted by Perraud et al, many TBDTs were identified also in our samples.…”
Section: Discussionmentioning
confidence: 90%
“…It has been shown that the presence of exosiderophores clearly impacts the expression levels of the proteins of the different iron uptake pathways of P . aeruginosa (Llamas et al ., , ; Perraud et al ., ).…”
Section: Regulationmentioning
confidence: 97%
“…This question needs to be investigated further in the future at the level of diverse communities involving different Pseudomonads but also other bacterial species since P. aeruginosa is able to use many different siderophores produced by other bacteria (exosiderophores) (Cornelis and Matthijs, 2002;Cornelis and Dingemans, 2013). It has been shown that the presence of exosiderophores clearly impacts the expression levels of the proteins of the different iron uptake pathways of P. aeruginosa (Llamas et al, 2006(Llamas et al, , 2008Perraud et al, 2020).…”
Section: Regulationmentioning
confidence: 99%
“…For example, P. aeruginosa carries genes within its genome for at least 20 different iron-uptake strategies [ 12 ]: (i) one ferrous (Fe 2+ ) iron uptake pathway, (ii) three heme acquisition pathways, (iii) ferric iron (Fe 3+ ) uptake pathways by the two siderophores pyoverdine (PVD) and pyochelin (PCH), produced by the pathogen itself, and (iv) at least 10 different “siderophore piracy” strategies to uptake Fe 3+ using xenosiderophores (siderophores produced by other bacteria). Indeed, most bacteria can use siderophores produced by other bacteria in multispecies communities and during infections by expressing compatible transporters that are able to capture and import ferric complexes they cannot synthesize themselves [ 13 , 14 , 15 , 16 ]. Except for ferrous-iron uptake, bacterial iron-uptake pathways always include an outer membrane transporter (OMT) involved in ferri-siderophore or heme uptake, enzymes involved in iron release from the siderophore or heme, and inner membrane transporters (ATP Binding cassette transporters of proton motive force-dependent permeases).…”
Section: Introductionmentioning
confidence: 99%